2020
DOI: 10.1002/jmv.26459
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression symptoms after virological clearance of COVID‐19: A cross‐sectional study in Milan, Italy

Abstract: Prevalence of anxiety/depression was investigated in 105 COVID‐19 patients at 1‐3 months from virological clearance by Hospital Anxiety and Depression Scale (HADS‐A/D). 30% of patients displayed pathological HADS‐A/D, 52.4% showed persistent symptoms. Pathological HADS‐A/D patients more commonly reported symptom persistence, even after adjustment for age, gender, disease severity. Psychological assessments should be encouraged in COVID‐19 patients’ follow‐up. This article is protected by copyright. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
164
1
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(184 citation statements)
references
References 13 publications
12
164
1
7
Order By: Relevance
“…Across both hospitalised and non-hospitalised populations, the most frequently reported symptoms were breathlessness, found in 13 studies (46%), [9,2831,3539,47,48,53] followed by persisting smell and taste disturbance documented in 12 studies (43%) [2528,3335,39–41,47,53] and fatigue in 11 studies (39%). [9,28,29,34,37,39,42,44,49,50,53] Psychological symptoms were also frequently reported, of which anxiety was most common (25%), [29,38,43,44,47,49,52] followed by depression, [38,43,44,47,52] sleep disorders, [28,38,42,52] and post-traumatic stress disorder (PTSD). [43,44,52] Increased dependency in activities of daily living (ADLs), comprising personal care and social activities, was reported by almost half of participants in one study (47.5%, 49/103), [46] as well as reduced quality of life (QoL).…”
Section: Resultsmentioning
confidence: 99%
“…Across both hospitalised and non-hospitalised populations, the most frequently reported symptoms were breathlessness, found in 13 studies (46%), [9,2831,3539,47,48,53] followed by persisting smell and taste disturbance documented in 12 studies (43%) [2528,3335,39–41,47,53] and fatigue in 11 studies (39%). [9,28,29,34,37,39,42,44,49,50,53] Psychological symptoms were also frequently reported, of which anxiety was most common (25%), [29,38,43,44,47,49,52] followed by depression, [38,43,44,47,52] sleep disorders, [28,38,42,52] and post-traumatic stress disorder (PTSD). [43,44,52] Increased dependency in activities of daily living (ADLs), comprising personal care and social activities, was reported by almost half of participants in one study (47.5%, 49/103), [46] as well as reduced quality of life (QoL).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the prevalence of significant PTSD was 12% ( Liu et al 2020 ). In another study, one-third of the patients with COVID-19 infection reported clinically significant anxiety and/or depression, at a median of 46 days after the virus clearance ( Tomasoni et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…While delirium, insomnia, and symptoms of depression, anxiety, and posttraumatic stress disorder (PTSD) have been reported as common features in the acute (and immediate convalescent) period, data are sparse on the psychiatric status in the post-illness phase ( Rogers et al 2020 ). To our knowledge, only three studies investigated the psychiatric symptomatology inpatients who had recovered from the acute COVID-19 infection, and these reported high rates of insomnia, and symptoms of PTSD, depression, and anxiety, about one month after the infection ( Liu et al 2020 ; Mazza et al 2020 ; Tomasoni et al 2020 ). These preliminary findings suggest substantial psychiatric morbidity following the COVID-19 infection, comparable to what was reported after the previous coronavirus epidemics (Severe Acute Respiratory Syndrome (SARS) and Middle East Respiratory Syndrome (MERS) (Wu et al 2020; Mak et al 2009; Lee et al 2007)).…”
Section: Introductionmentioning
confidence: 99%
“…There is a need for long-term follow up of patients with COVID-19, and especially those that have suffered ARDS, complications and ICU stay, for anxiety, depression, OCD and PTSD. For example, in one study, 107 COVID-19 patients in Milan, Italy were administered HADS to screen for anxiety and depression after viral clearance (Tomasoni et al 2021). From these patients, 30% had HADS results indicative of anxiety and depression.…”
Section: D)mentioning
confidence: 99%